The two waves of virtual reality in artistic practice. Issue 2 (1st October 2021) - Doyle, Denise
As the title of this article suggests, there appears to be two distinct waves of artistic engagement with virtual reality (VR) in artistic practice: the first during the initial technological development in the 1990s that enabled VR to become accessible to artists such as Char Davies and Toni Dove among others and the current second wave that has been based on a much greater accessibility of immersive headsets for artists and a wider general public, driven by both market forces and technological development. The term 'virtual reality' has been interchangeably used to mean virtual environments and virtual worlds, but here the aim is to solely examine the use of VR in artistic practices, where the intention is for the participant to largely experience the virtual space through total immersion, reserving the analysis of the mixed use of VR within mixed-reality environments to another study. The article begins with a brief history of the development of VR and an analysis of the key works created in what can be termed the first wave, before discussing the current use of VR in contemporary practices through the notion of affect in VR.